Thoughts on Pompeii’s Fine Ware Supply - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2017)
In recent years I have worked on the pottery from excavations below the levels of AD 79 on three sites in Pompeii and its surroundings, for which the pottery reports are completed or close to termination. This work led me to consider the sources of supply of fine wares to Pompeii.